Corporate Social Responsibility in Educational Programme among Malaysian Primary Schools: Perspectives from Corporate Companies in Malaysia - Athirah, Azhar; Azlinda, Azman (2021)
This study was conducted to acquire the corporate companies’ perspectives on educational programmes under their Corporate Social Responsibility (CSR) initiatives. It was found out that very little research on educational programmes conducted under CSR initiatives. The aims of the study; therefore, to identify the goals of CSR educational programmes initiatives in rural primary school, to highlight the impact of CSR educational programmes initiatives to the pupils and rural primary school from corporate perspectives; and; to highlight corporate companies’ suggestions in reaching out to more rural schools. Qualitative research method was chose by interviewing five corporate companies which were purposively selected. This exploratory study was analysed based on themes that emerged such as educational programmes goals, impact on pupils, impact on rural primary schools and concern from corporate companies. Findings revealed that the main educational programmes goal is to improve the educational achievement in school. This is by having motivational and team building programmes, educational support programmes, environmental programmes for pupils; training and development for teachers; and motivational talks for parents. Corporate companies stated that participated pupils in CSR educational programmes, have made teachers, school and their parents proud. It was due to improvements among participated pupils by achieving good and better grades in academics and gained self-confidence. Thus, schools were contented that the school ranking has improved. Corporate companies did express their concern on the sustainability of the programme once the educational programme ended. This study concluded that educational programmes under CSR initiatives have given good impact to pupils and schools but, there was no presence of educational programme sustainability in a long-term towards both pupils and school.